Reduced-order perfect nonlinear observers of fractional descriptor discrete-time nonlinear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this work is to propose and characterize fractional descriptor reduced-order perfect nonlinear observers for a class of fractional descriptor discrete-time nonlinear systems. Sufficient conditions for the existence of these observers are established. The design procedure of the observers is given and demonstrated on a numerical example.
Keywords: fractional; descriptor; nonlinear; discrete-time; design; reduced-order; perfect observer